Pengembangan Media Lembar Kerja Peserta Didik (LKPD) Menggunakan Pendekatan Kontekstual Pada Pembelajaran Geografi Materi Sumber Daya Alam SMA Negeri 1 Mootilango - Ismail, Iki; Eraku, Sunarty S; Lahay, Rakhmat Jaya (-, 2025)
IKI ISMAIL. 2024. This research is media development research conducted at SMA Negeri 1Mootilango, Mootilango District, Gorontalo Regency. This research aims to determine the feasibility of contextual-based student worksheets in learning geography on Natural Resources material in geography subjects at SMA Negeri 1 Mootilango. The research was carried out using the Addie development model, which has the following development stages: a) analysis stage; b) planning stage; c) development stage; d) implementation stage; e) evaluation stage. The subjects of this research were Class XI geography subject teachers at SMA Negeri 1 Mootilango and Class XI students at SMA Negeri 1 Mootilango. The research object used as material in conducting this research is LKPD which can be used as a learning medium.The types of data used in this research are quantitative and qualitative data. Data collection techniques are carried out through questionnaires, observation and documentation. The research instruments used were media utilization validation sheets, student response questionnaire sheets, lesson plans, and LKPD. The data analysis technique used is media utilization validation sheet analysis and student response analysis. The research results showed that validation of learning media by material experts obtained a score of 80%, including the "valid" qualification. The results of the validation of learning media by media experts gave a score of 85.7%, including the "very valid" qualification.The students' answers obtained a percentage score of 88.1%, including in the "strongly agree" category, while the validation results by the geography teacher obtained a score of 80%. The learning process related to natural resource material is facilitated using LKPD-based learning resources. The student response value in class XI IPS was 88.1%, indicating that LKPD-based learning media is very suitable for students to use in learning related to natural resource material